BIOGEOGRAPHY OF THE NORTHERN PERI-TETHYS FROM THE LATE EOCENE TO THE EARLY MIOCENE: PART 1. LATE EOCENE - Popov S.V.; Akhmetiev M.A.; Bugrova E.M.; Lopatin A.V.; Amitrov O.V.; Andreeva-Grigorovich A.S.; Zherikhin V.V.; Zaporozhets N.I.; Nikolaeva I.A.; Krasheninnikov V.A.; Kuzmicheva E.I.; Sytchevskàya E.K.; et al. (My University, 2001)
This monograph consists of three parts. The first part discusses principles and techniques of modern biogeography that are applicable to paleontological material. Data on zonation of the modern-day water area based on planktonic and benthic organisms are given, and the phytogeography of Western Eurasia and its main divisions are characterized. The main part Biogeography of the Late Eocene briefly considers the stratigraphy of the Upper Eocene, including data on the Priabonian of the stratotype region of Northern Italy and on the stratigraphy of the Alpine-Carpathian and Greater Caucasian basins. The paleogeography of these basins is described and illustrated by a paleogeographic map (Popov and Shcherba). Subsequently, the biogeography of the Ancient Mediterranean and Paleo-Paratethys is considered in detail on the basis of plankton, including planktonic foraminifers (Krasheninnikov), nannoplankton (Andreeva-Grigorovich), dinocysts (Akhmetiev, Andreeva-Grigorovich, and Zaporozhets), marine ichthyofauna (Sytchevskaya), and benthos, i.e., small benthic foraminifers and nummulitids (Bugrova), ostracodes (Nikolaeva), mollusks (Amitrov and Popov), and corals (Kuzmicheva). The biogeography of the surrounding landmasses is considered based on the terrestrial flora (Akhmetiev and Zaporozhets); insects (Zherikhin), terrestrial vertebrates (Lopatin), and freshwater ichthyofauna (Sytchevskaya). In the section Latitudinal-Climatic Zonation, the climate is reconstructed based on various groups of plankton, benthos, and flora. The time of the onset of the fall in temperature at the end of the Eocene, and the accompanying reduction of biodiversity, are considered. In the conclusion, the tectonic, paleogeographic, and climatic events that resulted in the fundamental reorganization of the biota of the Northern Peri-Tethys, extinction of the extremely rich fauna that existed in the early half of the Paleogenc, and the replacement of the Paleocenophytic flora with the Neocenophytic, are considered.
Keywords: Biogeography; Eocene; Western Eurasia; Peri-Tethys; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен